Comparative effectiveness and complications of intravenous ceftriaxone compared with oral doxycycline in Lyme meningitis in children: a multicentre prospective cohort study - Lise E Nigrovic; Thomas H Chun; John J Halperin; Sara E Vargas; Aisling R Caffrey; Jonathan A Race; Ulrike Ott; Brynna L Morrison; Bethany J Fuller; John M VanBuren; Pedi Lyme Net (BMJ Open)
Introduction Lyme disease is the most common vectorborne disease in the Northern hemisphere with more than 400 000 new cases in the USA annually. Lyme meningitis is an uncommon but potentially serious clinical manifestation of Lyme disease. Intravenous ceftriaxone had been the first-line treatment for Lyme meningitis, but is associated with a high rate of complications. Although efficacy and effectiveness (or real-world evidence) data for oral doxycycline are limited, practice guidelines were recently expanded to recommend either oral doxycycline or ceftriaxone as first-line treatments for Lyme meningitis. Our goal is to compare oral doxycycline with intravenous ceftriaxone for the treatment of Lyme meningitis on short-term recovery and long-term quality of life.Methods and analysis We are performing a prospective cohort study at 20 US paediatric centres located in diverse geographical range where Lyme disease is endemic. The clinical care team will make all antibiotic treatment decisions for children with Lyme meningitis, as per usual practice. We will follow enrolled children for 6 months to determine time of acute symptom recovery and impact on quality of life.Ethics and dissemination Boston Children’s Hospital, the single Institutional Review Board (sIRB), has approved the study protocol with the other 19 enrolling sites as well as the Utah data coordinating centre relying on the Boston Children’s Hospital sIRB. Once the study is completed, we will publish our findings in a peer-reviewed medical journal.